Polynomial error approximation of a precision angle measuring system - Šiaudinytė, Lauryna; Bručas, Domantas; Rybokas, Mindaugas; Kulvietis, Genadijus (Geodesy and Cartography, 2013)
The paper deals with the calibration of a flat angle measuring system. The article describes a comparative method for using a multi-angular prism (polygon) with autocollimator along with an angle measuring system. The components of angle measuring system is analysed in the paper. The article also presents polynomial error approximation and the obtained results of calibrating the precision angle measuring system as well as discusses preliminary assumptions for further research.